Hepatoprotective effects of methanol extract of Carissa opaca leaves on CCl4-induced damage in rat - Khan Rahmat A; Khan Muhammad R; Sahreen Sumaira (BMC, 2011)
Abstract Background Carissa opaca (Apocynaceae) leaves possess antioxidant activity and hepatoprotective effects, and so may provide a possible therapeutic alternative in hepatic disorders. The effect produced by methanolic extract of Carissa opaca leaves (MCL) was investigated on CCl4-induced liver damages in rat. Methods 30 rats were divided into five groups of six animals of each, having free access to food and water ad libitum. Group I (control) was given olive oil and DMSO, while group II, III and IV were injected intraperitoneally with CCl4 (0.5 ml/kg) as a 20% (v/v) solution in olive oil twice a week for 8 weeks. Animals of group II received only CCl4. Rats of group III were given MCL intragastrically at a dose of 200 mg/kg bw while that of group IV received silymarin at a dose of 50 mg/kg bw twice a week for 8 weeks. However, animals of group V received MCL only at a dose of 200 mg/kg bw twice a week for 8 weeks. The activities of aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), lactate dehydrogenase (LDH) and γ-glutamyltransferase (γ-GT) were determined in serum. Catalase (CAT), peroxidase (POD), superoxide dismutase (SOD), glutathione-S-transferase (GST), glutathione peroxidase (GSH-Px), glutathione reductase (GSR) and quinone reductase (QR) activity was measured in liver homogenates. Lipid peroxidation (thiobarbituric acid reactive substances; TBARS), glutathione (GSH) and hydrogen peroxide (H2O2) concentration was also assessed in liver homogenates. Phytochemicals in MCL were determined through qualitative and high performance liquid chromatography (HPLC) analysis. Results Hepatotoxicity induced with CCl4 was evidenced by significant increase in lipid peroxidation (TBARS) and H2O2 level, serum activities of AST, ALT, ALP, LDH and γ-GT. Level of GSH determined in liver was significantly reduced, as were the activities of antioxidant enzymes; CAT, POD, SOD, GSH-Px, GSR, GST and QR. On cirrhotic animals treated with CCl4, histological studies showed centrilobular necrosis and infiltration of lymphocytes. MCL (200 mg/kg bw) and silymarin (50 mg/kg bw) co-treatment prevented all the changes observed with CCl4-treated rats. The phytochemical analysis of MCL indicated the presence of flavonoids, tannins, alkaloids, phlobatannins, terpenoids, coumarins, anthraquinones, and cardiac glycosides. Isoquercetin, hyperoside, vitexin, myricetin and kaempherol was determined in MCL. Conclusion These results indicate that MCL has a significant protective effect against CCl4 induced hepatotoxicity in rat, which may be due to its antioxidant and membrane stabilizing properties.